REVITALIZING AGRICULTURE: CULTIVATION INNOVATIONS IN INDIA'S NORTHEAST REGION (International Journal of Food and Nutritional Sciences, 2022)
The changing agricultural landscape in Nagaland, part of India's Northeast region, has led to intriguing shifts in crop preferences and production trends. Cultivation innovations play a vital role in transforming agriculture, involving high-yield crop varieties, advanced practices, and crop diversification for resilience. The study emphasized the role of expanded cultivation areas in boosting food crop production. The secondary data sources obtained from Agriculture Directorate Economics and Statistics survey report were examined to identify trends in the cropped area, production, and yield for major crop types in Nagaland over a specified period. The study revealed a remarkable 71% growth in gross cropped area from 1998-1999 to 2012-13, highlighting the increasing significance of agriculture. Significant progress in irrigation facilities, covering 22% of the net sown area, was observed. Crop preferences showed a decline in foodgrain dominance, with rice decreasing from 80.3% in 1999-2000 to 68.9% in 2014-15. Conversely, oilseeds and pulses gained prominence, while non-cotton fibre crops and pulses witnessed notable production growth. However, Cotton production faced a considerable decline during the same period. Overall, it concluded the need to adopt strategies for agricultural revitalization in Nagaland, addressing challenges faced by declining crops like Cotton, promoting high-yield varieties, and implementing innovative agricultural practices for sustainable development. Cultivation innovations are essential for enhancing the resilience of the agricultural sector and ensuring food security in the region